2021
DOI: 10.1371/journal.pone.0260667
|View full text |Cite
|
Sign up to set email alerts
|

A worldwide systematic review and meta-analysis of bacteria related to antibiotic-associated diarrhea in hospitalized patients

Abstract: Introduction Antibiotic-associated diarrhea (AAD) is a major hospital problem and a common adverse effect of antibiotic treatment. The aim of this study was to investigate the prevalence of the most important bacteria that cause AAD in hospitalized patients. Materials and methods PubMed, Web of Science and Scopus databases were searched using multiple relevant keywords and screening carried out based on inclusion/exclusion criteria from March 2001 to October 2021. The random-effects model was used to conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 76 publications
0
10
0
2
Order By: Relevance
“…Antibiotic-associated diarrhoea is a commonly observed side effect among patients medicated with antibiotic therapy [ 8 , 9 ]. In most cases, the diarrhoea is mild and requires no treatment; it clears up within a few days or after therapeutic completion [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic-associated diarrhoea is a commonly observed side effect among patients medicated with antibiotic therapy [ 8 , 9 ]. In most cases, the diarrhoea is mild and requires no treatment; it clears up within a few days or after therapeutic completion [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic-associated diarrhoea is a commonly observed side effect among patients medicated with antibiotic therapy [ 8 , 9 ]. In most cases, the diarrhoea is mild and requires no treatment; it clears up within a few days or after therapeutic completion [ 9 ]. Under this presumptive diagnosis, other protozoal infections might be neglected from the diagnostic consideration as had occurred in our case.…”
Section: Discussionmentioning
confidence: 99%
“…По данным Всемирной организации здравоохранения, ГИЭ являются одной из основных причин смерти и инвалидизации детей в возрасте до 5 лет. Распространенность ГИЭ в России, по разным данным, -от 15,6 до 38 на 1000 среди доношенных новорожденных [3].…”
Section: источники информацииunclassified
“…нфекция Clostridioides difficile (CDI), ранее известная как Clostridium difficile, является во всем мире ведущей причиной ААД, которая часто возникает во время или после лечения антибактериальными препаратами [1]. Ее частота варьирует от 5% до 25% в зависимости от типа используемого антибиотика [2,3]. В последние годы от-мечается дальнейший рост ААД, ассоциированный как с внебольничной, так и внутрибольничной инфекцией [4,5].…”
unclassified
“…Antibiotic-associated diarrhea (AAD) continues to be a major healthcare issue, both in hospitalized patients and in the community (5). Many investigations have revealed that C. perfringens played an important role in diarrheic patients with a history of antibiotic use (6, 7). According to some studies, C. perfringens is responsible for 5 to 20% of all cases of AAD and sporadic non-foodborne diarrhea (6, 8).…”
Section: Introductionmentioning
confidence: 99%